Sexual dimorphism in epicuticular compounds despite similar sexual selection in sex role‐reversed seed beetles. (12th September 2017) - Booksmythe, I.; Rundle, H. D.; Arnqvist, G.
Abstract: Sexual selection imposed by mating preferences is often implicated in the evolution of both sexual dimorphism and divergence between species in signalling traits. Epicuticular compounds (ECs) are important signalling traits in insects and show extensive variability among and within taxa. Here, we investigate whether variation in the multivariate EC profiles of two sex role‐reversed beetle species, Megabruchidius dorsalis and Megabruchidius tonkineus, predicts mate attractiveness and mating success in males and females. The two species had highly distinct EC profiles and both showed significant sexual dimorphism in ECs. Age and mating status in both species were also distinguishable by EC profile. Males and females of both species showed significant association between their EC profile and attractiveness, measured both as latency to mating and as success in mate‐choice trials. Remarkably, the major multivariate vector describing attractiveness was correlated in both species, both sexes, and in both choice and no‐choice experiments such that increased attractiveness was in all cases associated with a similar multivariate modification of EC composition. Furthermore, in both sexes this vector of attractiveness was associated with more male‐like EC profiles, as well as those characterizing younger and nonvirgin individuals, which might reflect a general preference for individuals of high condition in both sexes. Despite significant sexual selection on EC composition, however, we found no support for the proposition that sexual selection is responsible for divergence in ECs between these species.